Electrochemical Protein Cleavage in a Microfluidic Cell for Proteomics Studies. (2017) - van den Brink, Floris T.G.; Zhang, Tao; Ma, Liwei; Odijk, Mathieu; Olthuis, Wouter; Permentier, Hjalmar P.; Bischoff, Rainer P.H.; van den Berg, Albert
Abstract: Electrochemical protein digestion prior to mass spectrometric analysis is a purely instrumental approach to protein identification, offering reduced consumption of chemicals and shorter analysis times compared to the use of enzymes and chemical cleavage agents. Here we demonstrate the possibilities of site-specific peptide bond cleavage and disulphide bond reduction in a microfluidic electrochemical cell. The use of microfluidics in this context is beneficial for increased electrochemical cleavage yields, small sample volumes and the possibility of rapid on-line analysis, thereby providing a versatile tool for routine proteomics studies.